Environmental liability and ecological damage in European law / edited by Monika Hinteregger. - Hinteregger, Monika (Common core of European private law., 2008)
Providing a comprehensive analysis of environmental liability law in Europe, this book offers a general introduction to the status of environmental liability in Europe. It describes the relevant international treaties and the EC-Environmental Liability Directive and discusses the conflict of laws issues regarding transfrontier environmental damage. It also contains the results of a comparative project covering 14 jurisdictions in 13 European countries (Austria, Belgium, England and Wales, Finland, France, Germany, Greece, Ireland, Italy, Netherlands, Portugal, Scotland, Spain, Sweden) on the private law aspects of environmental liability. It addresses the main problems of the application of tort law in environmental law, such as the availability of non-fault liability, the establishment of causation, the scope of available remedies and the issue of legal standing. Due to the very limited harmonizing effect of the EC-Environmental Liability Directive national tort law will keep its importance in the field of environmental liability.